Levinas Concordance - Ciocan, Cristian; Hansel, Georges; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This work is the first Levinas Concordance. The particularity of this index is that it covers on all the 28 books published by Levinas in French. The Levinas Concordance comprises the complete list of meaningful words of Levinas' oeuvre and their corresponding occurrences, indicated by book, page and line. The Levinas Concordance contains eight specific indexes: General Index of French Terms; General Index of Proper Names; Index of Hebrew, Biblical and Talmudic Proper Names; Index of Hebrew Terms; Index of Greek Terms; Index of Latin Terms; Index of German Terms; Index of Works.
List of Abbreviations -- General Index of French Terms -- General Index of Proper Names -- Index of Hebrew, Biblical and Talmudic Proper Names -- Index of Hebrew Terms -- Index of Greek Terms -- Index of Latin Terms -- Index of German Terms -- Index of Works.
Keywords: PHILOSOPHY (GENERAL).; ETHICS; PHILOSOPHY, MODERN; ONTOLOGY; PHENOMENOLOGY; PHILOSOPHY; PHILOSOPHY; PHENOMENOLOGY; ETHICS; PHILOSOPHY OF RELIGION; MODERN PHILOSOPHY; ONTOLOGY